PENGUJIAN TERHADAP KADAR GAS FORMALIN DI RUANG PRAKTIKUM LABORATORIUM ANATOMI FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM INDONESIA (UII) (Studi level Toksisitas Dibandingkan Dengan Standar Nilai Ambang Batas) - Raden Edi Fitriyanto; Zainuri Sabta Nugraha (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2009)
Formaline solvent is widely used in life, example as a preservative cadaver in anatomy laboratory. Forma line solvent can evaporate easily, in the form of gas it should be react with mucous layer quickly, especially at respiratory tract. In human body, it is oxidated become formic acid, especially in the cells of liver and red blood. In many earlier researches, the short-term exposure caused irritation to the local mucous surface of eyes, nose and up respiratory tract. However, the long term exposure caused tumor growth in the rat nose, pulmonary t issue damage and asthma reactions in sensitive individuals. The aim of the study is to measure forma line gas concentration and comparing the result with Thresold Limit Value (TLV) that safety for health. The research is nonexsperimental study with associative analysis. The research objects were practice space, storage cadaver space and lobby of Anatomy Laboratory. The research subjects were divided into 3 phases of measurement, phase I is measurement in the athmosphere (control), phase II is measurement in practice space laboratory during activities and phase Ill is measurement in practice space laboratory with no activities. Formaline gas concentration in practice space Anatomy Laboratory is under the TLV (TLV: 0.3 ppm) with no activities. Duringactivities, it is over the TLV: in preparation space 0,99569 ppm and practise space 0,37804 ppm. Formaline gas concentration in practice space during activities is over the TLV. It is a risk to cause some health disorders, especially to user and staff of the laboratory. It need good planning of practise programs and design of anatomy laboratory based on safety.